Health workers' perception about the supplemental immunization activities in Gombe Local Government Area, Gombe State. (2007)
Polio immunization has faced challenges of refusal from care givers in recent times despite the efforts put in to ensure its success. To identify the role of service providers in this attitudinal shift, a survey describing the perception of health workers about the supplemental immunization activities was carried out among 265 health workers who participated in the 3rd round of the 2003 sub-national immunization days in Gombe local government area (LGA) of Gombe state, Nigeria: Data was collected using pretested qualitative and quantitative instruments. Quantitative data was analysed using EPI Info statistical software and the qualitative using thematic areas. Results showed that 211 (79.6%) knew fecaloral route as the commonest mode for poliovirus transmission, 231(87.2%) knew the age for vaccination, 224(84.5%) knew the correct use of vaccine vial monitor while 143(53.9%) knew the correct action to take when a case of polio was identified. On perception, 22(8.3%) perceived that OPV was harmful due to repeated administration, 26(9.8%) perceived that OPV had sterility property, contained harmful materials 14(5.3%) and HIV 11(4.2%). Main reasons for immunization rejection were sterility 115(43.3%) and contamination with HIV 94(35.5%). The study found that irrespective of adequate knowledge on transmission, misconceptions still exist among health workers of the polio vaccine. Based on this, there is the need for continuous training to remove the misconceptions concerning their perceptions and rumors about the vaccine and the programme.